Co-occurrence of different insect species in oviposition media of black soldier fly, Hermetia illucens (Diptera: Stratiomyidae) - Hadura Abu Hasan; Fitree Dina (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2019)
The black soldier fly (BSF), Hermetia illucens (Diptera: Stratiomyidae) is well known as a non-pest tropical insect which is distributed in warm temperature and tropic regions. The larvae of this species consume mainly on decomposing organic materials. In this study, fermented coconut waste (CW) was used as oviposition media for black soldier fly. For each sampling, the oviposition media were placed inside five (5) black bins (43 cm diameter x 50 cm height) for ten days in Taman Flora, School of Biological Sciences, Universiti Sains Malaysia (USM). There was co-occurrence of other insect species found in oviposition media of black soldier fly. A total of 3554 insects belonging to four (4) orders were encountered during the study period of eight months, namely, Blattidae, Coleoptera, Diptera and Hymenoptera. Highest number of individuals was recorded from the order Diptera of the family Drosophilidae (N=1890, 53.18%) and followed by the family of Phoridae (N=1350, 37.99%). The percentage of insect species occurred in the following order, Epunaea luteolus (3.71%) ˃ Scarabaeidae (3.38%) ˃ Oecophylla smaragdina (0.90%) ˃ Symploce pallens (0.59%) ˃ Periplaneta fuliginosa (0.23%) ˃ and Paederus littoralis (0.03%). The finding of this study is of great important to identify the multiple species of insects that contribute either as visitor, decomposer, competitor, or predator to the black soldier fly colony.